Building The Profile of Pancasila Students Through a Tolerance Learning Project : A Case Study in Sukowono Village as a Pancasila Village from a Global - Indratmoko, Johanes Agung; Ali, A Zulkarnain; Cahyono, Arie Eko (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2025)
This research examines the importance of strengthening character education based on Pancasila values in addressing the challenges of diversity in Indonesia. The focus is on integrating tolerance and global diversity values into the formation of the Pancasila Student Profile, which aims to enable students to live harmoniously in a multicultural society. Using a case study in Sukowono Village, known as Pancasila Village, this research identified best practices in tolerance-based character education, such as interfaith cooperation and joint celebrations of religious holidays. This qualitative research approach involved participatory observation, in-depth interviews, and document analysis to explore how Pancasila values, especially tolerance, were implemented in community life and formal education. The data were analyzed using Miles and Huberman’s interactive model, which includes data reduction, data display, and conclusion drawing and verification. The study proposes an effective project-based learning model to internalize tolerance values in education. This model included stages such as introducing the concept of tolerance, field visits to places of worship, interfaith collaborative projects, and experience reflection. The research results showed that this learning model successfully enhanced students' understanding of the importance of tolerance and diversity, shaping more inclusive students who are prepared to face global challenges. These findings are expected to serve as a guide for educators and policymakers in developing curricula that support the character formation of Pancasila Students throughout Indonesia.